METHODOLOGY FOR COUNSELLING STUDENTS OF VOCATIONAL EDUCATION ON YOUTH ENTREPRENEURSHIP IN THE CONTEXT OF IMPLEMENTING SUSTAINABLE DEVELOPMENT GOALS (Innovative professional education, 2024)
It is substantiated that the implementation of Sustainable Development Goal 8 in Ukraine, which directs the policy of states to achieve decent work and economic growth, will be facilitated by preparing future skilled workers for self-employment by starting and running their own business. The article presents a methodology for counselling vocational education students on youth entrepreneurship and a corresponding set of educational and methodological support developed by the Laboratory of ProfessionalCareer of the Institute of Vocational Education of the National Academy of Pedagogical Sciences of Ukraine. The probable socio-economic effect of its implementation in vocational education institutions is predicted (reduction of unemployment and reductionof state subsidies for the maintenance of the unemployed; increase in the number of legal small enterprises and growth of revenues to the state budget; development of a network of small enterprises in each region, which in wartime proved to be the most mobile and capable of rapid restoration of logistics chains; stabilisation of the psychological state of young people in conditions of military uncertainty through the formation of readiness to perceive.
Keywords: vocational education, sustainable development of society, entrepreneurship, entrepreneurial competence, counseling on youth entrepreneurship